KEBEBASAN BERAGAMA DALAM HUBUNGANNYA DENGAN HAK ASASI MANUSIA DAN DEMOKRASI (Pandangan Tokoh Agama, Akademisi dan Penggiat HAM di Kota Palembang) - Rr Rina Antasari (An Nisa'a, 2014)
Talking about the "freedom" that is rooted in the word has several senses, such as: loose at all, apart from the demands, liabilities and feelings of fear, not be punished, not bound or limited by rules and independent. From that sense would be able to make an impression that the lack of recognition of the rights of people. Furthermore, the adage that freedom be freely interpreted relativism trapped in a box.ملخص: الحديث عن "الحرية" التي تعود جذورها إلى كلمة ديها العديد من الحواس، مثل: فضفاضة على الإطلاق، بغض النظر عن المطالب والالتزامات ومشاعر الخوف، لا يعاقب، ليست ملزمة أو تقتصر بقواعد ومستقلة. من هذا المنطلق ستكون قادرة على خلق انطباع أن عدم الاعتراف بحقوق الناس. وعلاوة على ذلك، فإن القول المأثور أن حرية تفسيرها بحرية نسبية المحاصرين في صندوق.